Species of Ancistrus (Siluriformes, Loricariidae) from Ecuador, with the description of a new species from the Amazon River Basin - Provenzano R., Francisco; Barriga-Salazar, Ramiro (Zootaxa, 2018)
To elucidate the species of the genus Ancistrus that inhabit freshwater systems of Ecuador, cataloged lots of the Fish Collection, Museo de la Escuela Politécnica Nacional (MEPN), in Quito, were analyzed. Four species were identified: Ancistrus alga (Cope, 1872), A. malacops (Cope, 1872), A. clementinae Rendahl, 1937, and a new species that herein is described. Ancistrus clementinae inhabits aquatic systems of the Pacific slope, mostly in the Guayas River drainage. The other three species live in freshwater systems that drain to the Amazon River Basin. Ancistrus alga inhabit the northern and central portions of eastern Ecuador. Ancistrus malacops has a broad distribution from north to south, but is absent from the Santiago River. Both species occasionally live in sympatry. The new species is restricted to the Santiago River, in Morona-Santiago province. Each species has unique external morphological features and/or a coloration pattern that allow unambiguous identification, at least of males. This paper provides a description of the new species, and a re-description and images of the other three.